Excited state absorption in KCI:EU2+ - Schinca, Daniel Carlos (1994)
Non-linear behavior with respect to exciting fluence of both photoacoustic and luminescent signals in KCI:Eu(2+) , excited by laser pulses at 355 nm, were analyzed in terms of excited state absorption (ESA). Measured ESA cross-sections for 355 and 420 nm were found to be 1×10(−17)cm2 and 2×10(−18)cm2 respectively.